Fouling of microfiltration membranes by biopolymers. Issue 8 (23rd May 2016) - Vu, Anh; Darvishmanesh, Siavash; Marroquin, Milagro; Husson, Scott M.; Wickramasinghe, S. Ranil
ABSTRACT: Suppression of fouling due to biopolymers of relevance to the brewing industry has been investigated. The effects of three model biopolymers: casein (protein), catechin (polyphenol), and dextran (polysaccharide) on fouling of asymmetric 0.65 μm polyethersulfone membranes during direct-flow filtration have been studied. While dextran is successful in disrupting interactions between casein and catechin, the associated reduction in aggregate size does not always result in reduced fouling. Solution conditions such as pH and ionic strength modulate the tendency of the aggregates to adsorb onto the membrane surface. Thus, optimizing solution conditions to suppress adsorption of aggregates is essential for increasing the membrane filtration capacity.